Treatment of epidermoid tumors with gamma knife radiosurgery: case series (2016)
Epidermoid tumors (ETs) are benign lesions that are treated mainly by means of surgical resection, with overall good results. External beam radiotherapy is an alternative treatment for those recurrent tumors, in which a second surgery might not be the best choice for the patient. A little information exists about the effectiveness of gamma knife radiosurgery for the treatment of newly diagnosed and recurrent ETs. We present three cases of ETs treated with gamma knife radiosurgery